Amyotrophic lateral sclerosis of long clinical course clinically presenting with progressive muscular atrophy. Issue 1 (3rd December 2018) - Matsubara, Tomoyasu; Oda, Masaya; Takahashi, Tetsuya; Watanabe, Chigusa; Tachiyama, Yoshiro; Morino, Hiroyuki; Kawakami, Hideshi; Kaji, Ryuji; Maruyama, Hirofumi; Murayama, Shigeo; Izumi, Yuishin
Abstract : Amyotrophic lateral sclerosis (ALS) primarily affects upper and lower motor neurons. Phosphorylated trans‐activation response DNA‐binding protein of 43 kDa (TDP‐43) inclusion bodies are reportedly a pathological hallmark of sporadic ALS. Here, we present an atypical case of sporadic ALS that progressed very slowly, persisted for 19 years, and clinically appeared to only affect the lower motor neurons; however, upper motor neuron degeneration was detected at autopsy. Furthermore, no inclusion bodies positive for phosphorylated TDP‐43, ubiquitin, fused in sarcoma, or superoxide dismutase‐1 were detected in the central nervous system. We performed exome‐sequencing data analysis but found no genetic disorders. This was therefore an unusual case of lower motor neuron‐predominant ALS without TDP‐43 pathology or known gene‐disease associations. We also reviewed autopsied ALS cases that progressed slowly and had no phosphorylated TDP‐43 or ubiquitin‐positive inclusions and present the clinicopathological features of such cases. Based on these results, there may be a sporadic ALS subgroup that progresses slowly and shows no accumulation of phosphorylated TDP‐43.